ANALISIS KESULITAN SISWA DALAM MEMBACA LANCAR DI SD NEGERI 5 SABU BARAT - Erlin Enjelik Novelia Ga Riwu; Gaspar Melo (Journal of Character and ELementary Education, 2022)
This study aims to describe the characteristics of fluency reading difficulties and the factors influencing students' reading fluency in grade III. This research was conducted at SD Negeri 5 West Sabu. The type of research used is descriptive qualitative. Data collection techniques used by researchers in this study were oral tests, interviews, observation, and documentation. The focus of the research in this study was the teacher and students while the research subjects were all 30 class III students at SD Negeri 5 West Sabu, with 18 female students and 12 male students. The results showed that the characteristics of fluency reading difficulties in class III were pronouncing words and sentences incorrectly, spelling, omitting letters and words, adding words, flat intonation and not paying attention to punctuation marks, unable to string letters together, reading haltingly and not understanding reading content. The factors that cause difficulty reading fluently are internal and external factors. Internal factors include (difficulty recognizing letters, eliminating letters and words, lack of interest in reading, and physical factors). While external factors include (how to teach teachers and family environment factors).